The choice of foreign locations of Swiss MNEs - Spyridon Arvanitis; Heinz Hollenstein; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2012)
In this paper, the parent firms' choice of FDI locations is analyzed based on a unique firm-level dataset for Swiss MNEs. The data allows a detailed characterization of parent companies, their foreign subsidiaries and the two-way trade flows between parent companies and foreign affiliates. In combination with information on the hosts regions of the FDI, the data allows to identify the factors determining the choice among nine alternative destinations. As firm-level studies are quite rare so far and, if available, are based on only few firm characteristics, this research provides substantial new insights.
Keywords: F2; 330; Foreign Direct Investment; Global Location Portfolios; Intra-Firm Trade; Direktinvestition; Multinationales Unternehmen; Intraindustrieller Handel; Schweiz